Atopic Dermatitis: Epidemiology and Clinical Phenotypes - Annunziata Raimondo; Serena Lembo (Mattioli1885, 2021)
Atopic dermatitis (AD) is a chronic, lifelong, relapsing condition. The wide spectrum of the possible clinical presentations, depending on patient's age, age of onset of disease, topography and morphology of dermatitis, limits the epidemiologic information on its prevalence and incidence. A clear definition of the different clinical AD phenotypes and epidemiology is essential for an appropriate patient's treatment and management, in particular for adults. This review summarizes the most recent epidemiologic data from the 21st century, on AD prevalence and incidence rates either in children or adults, with a special focus on their trends in Europe. Moreover, an effort to categorize diverse AD clinical expressions has been made, aiming to facilitate differential diagnosis and speed up the start of the correct therapy.